Microfacies, Depositional Model and Reservoir Characterization of Upper Cretaceous Kawagarh Formation, Qamar Mela Section, Nizampur Basin, Khyber Pakhtunkhwa, Pakistan. - Salman Ahmad Khattak; Samiullah Khan; Muhammad Salman (Jurnal Nasional Pengelolaan Energi MigasZoom, 2021)
The present study main focused on reservoir Characterization of the Upper Cretaceous Kawagarh Formation from Qamar Mela Section, Nizampur Basin. The samples were collected from the field by using standard procedures involving section measurement, lithological logging and photography. The collected samples were used to prepare the thin sections followed by petrographic analysis using Optika microscope in the laboratory. To explore the reservoir potential, we studied the impact of diagenesis on reservoir potential, supplemented by plug porosity and permeability, and SEM analysis. The outcrop is mainly composed of limestone and marl. Fifteen samples were studied from 45m thick section and two main microfacies were identified. The microfacies includes; (1). Mudstone microfacies (planktonic foraminiferal mudstone and dolomitic mudstone sub-microfacies), (2). Radiolarian bioclastic planktonic foraminiferal wackestone microfacies. The environment of deposition interpreted on the basis of microfacies for Kawagarh Formation is inner ramp to outer ramp and deep basinal settings. The Kawagarh Formation is also modified by various diagenetic features including compaction, dolomitization, dissolution, pyrite precipitation, cementation and spar filled fractures representing meteoric to marine phreatic with mixing zone and burial diagenetic environments. Dissolution, fracturing and dolomitization are the diagenetic processes which enhanced the porosity while cementation, pyrite precipitation and compaction decreased the porosity. Plug porosity and permeability of four rock samples averages 1.69% and 0.267 Ka/md, respectively. SEM analysis shows different types of porosity includes vuggy, shelter and intergranular. The low porosity and permeability levels of Kawagarh Formation suggest only a modest reservoir potential. The present study main focused on reservoir Characterization of the Upper Cretaceous Kawagarh Formation from Qamar Mela Section, Nizampur Basin. The samples were collected from the field by using standard procedures involving section measurement, lithological logging and photography. The collected samples were used to prepare the thin sections followed by petrographic analysis using Optika microscope in the laboratory. To explore the reservoir potential, we studied the impact of diagenesis on reservoir potential, supplemented by plug porosity and permeability, and SEM analysis. The outcrop is mainly composed of limestone and marl. Fifteen samples were studied from 45m thick section and two main microfacies were identified. The microfacies includes; (1). Mudstone microfacies (planktonic foraminiferal mudstone and dolomitic mudstone sub-microfacies), (2). Radiolarian bioclastic planktonic foraminiferal wackestone microfacies. The environment of deposition interpreted on the basis of microfacies for Kawagarh Formation is inner ramp to outer ramp and deep basinal settings. The Kawagarh Formation is also modified by various diagenetic features including compaction, dolomitization, dissolution, pyrite precipitation, cementation and spar filled fractures representing meteoric to marine phreatic with mixing zone and burial diagenetic environments. Dissolution, fracturing and dolomitization are the diagenetic processes which enhanced the porosity while cementation, pyrite precipitation and compaction decreased the porosity. Plug porosity and permeability of four rock samples averages 1.69% and 0.267 Ka/md, respectively. SEM analysis shows different types of porosity includes vuggy, shelter and intergranular. The low porosity and permeability levels of Kawagarh Formation suggest only a modest reservoir potential.